The synonymy of Cyalithoides fulgida Fisher, 1922 with Chrysodema robusta Deyrolle, 1864 (Coleoptera: Buprestidae: Chrysochroinae) - Bellamy, C. L.; Lander, T. (Zootaxa, 2008)
The genus Cyalithoides Fisher (1922) has remained unstudied since its original description, with only subsequent listings by Obenberger (1926) and Bellamy (2003). Furthermore, it was discussed apparently without the type having been examined by Levey (1978) and Hoyski (1980) in relation to new taxa and classification proposals in their respective works. The unique holotype of C. fulgida Fisher (1922) was recently examined by us and was found to be synonymous with Chrysodema robusta Deyrolle (1864), and structurally coming very close to the type of C. cyanivertex Obenberger (1928), which is also a junior synonym of C. robusta. Lander’s (2003) recent revision of Chrysodema Laporte & Gory, 1835 provides confidence for the new synonymy proposals below as there are no differences in C. robusta that do not agree with the current definition of Chrysodema. One additional note is that Fisher must have considered Cyalithoides as feminine given his use of fulgida, as the specific epithet. Article 30.1.4.4 (ICZN 1999) states that genus-group endings in the suffix -oides are masculine unless the author stated another gender or treated it otherwise. Although Bellamy (2003) treated Cyalithoides as masculine, it can be argued that Fisher treated it as feminine and that definition has priority. Nonetheless, with the synonymy proposed herein, C. fulgida is moved to another feminine genus.